Beyond Habitat: Memory Versus Environment in Shaping Animal Space Use - Tana L. Verzuh; Kevin L. Monteith; Tayler N. LaSharr; Cody F. Wallace; Rachel A. Smiley; Brittany L. Wagler; Chris Geremia; Katey S. Huggler; Hall Sawyer; Matthew J. Kauffman; Jerod A. Merkle (Ecology Letters, 2025)
For nearly half a century, ecologists have sought to explain animal space use through characteristics of the environment (i.e., habitat). Recent evidence suggests animals also use memory of previous experiences to decide when and where to move. Yet, the relative influence of the two in explaining animal space use has not been resolved. Using six large ungulate species in the Rocky Mountains (USA), we evaluated the performance of a habitat selection model with 16 environmental variables and another with two variables representing previous use (i.e., memory). While memory outperformed the environment for two species and the environment outperformed memory for four species, the influence of memory and the environment was overall comparable. The environment best explained the space use of specialists, while memory best explained species with strong site fidelity. Our work challenges traditional habitat selection theory, showcasing that animals build their spatial preferences through experience just as much as merely responding to their environment.

Temperament and state-dependent behaviours in large herbivores - Heather N. Abernathy; Rebecca L. Levine; Yasaman N. Shakeri; Jaron T. Kolek; Brittany L. Wagler; Rachel A. Smiley; Rhiannon P. Jakopak; Mitchell J. Brunet; Rebekah T. Rafferty; Seth T. Rankins; Katey S. Huggler; Brandon Scurlock; et al. (Animal Behaviour, 2025)

Influence of Adding Small Instream Wood on Fishes and Hydraulic Conditions in Channelized Agricultural Headwater Streams - Eric J. Gates; Peter C. Smiley (Fishes, 2024)
Instream wood is important for fish in headwater streams because it promotes the development of pool habitat and provides cover from predators during periods of low flow. The benefits of large instream wood (length > 1 m and diameter > 0.1 m) have been extensively documented, but little is known about the influence of small instream wood (length ≤ 1 m or diameter ≤ 0.1 m) on fish communities and hydraulic conditions (i.e., water depth, water velocity, wetted width, discharge, pool area) in channelized agricultural headwater streams in North America and Europe. Understanding the influence of small instream wood will provide information that can guide the development of novel management strategies for fishes within these degraded streams. We conducted a two-part field experiment in the summer of 2011 in channelized agricultural headwater streams in central Ohio, consisting of an initial instream wood survey to document the amounts and types of instream wood found in these streams, and then conducted a before–after–control–impact experiment where we sampled fishes and hydraulic variables before and after the addition of small instream wood to pools. The instream wood survey documented that instream wood density ranged from 0 to 0.29 pieces/m2, small simple pieces were the most frequently occurring type of instream wood, and parallel was the most frequently occurring instream wood orientation. The amount of instream wood was greater (p 0.450) in fish community structure or hydraulic variables occurred between control and treatment pools before or after the addition of small instream wood. Our results suggest the addition of large instream wood might be needed to elicit a fish community response, and it is possible to add instream wood to channelized agricultural headwater streams without impeding the downstream water flow.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Optogenetic manipulation of the prelimbic cortex during fear memory reconsolidation alters fear extinction in a preclinical model of comorbid PTSD/AUD - C. E. Smiley; J. T. McGonigal; K. E. Nimchuk; J. T. Gass (Psychopharmacology, 2021)

The infralimbic cortex and mGlu5 mediate the effects of chronic intermittent ethanol exposure on fear learning and memory - C. E. Smiley; J. T. McGonigal; T. Valvano; R. J. Newsom; N. Otero; J. T. Gass (Psychopharmacology, 2020)

Identification of quantitative trait loci (QTL) for resistance to Fusarium crown rot (Fusarium pseudograminearum) in multiple assay environments in the Pacific Northwestern US - G. J. Poole; R. W. Smiley; T. C. Paulitz; C. A. Walker; A. H. Carter; D. R. See; K. Garland-Campbell (Theoretical and Applied Genetics, 2012)

Differences in aquatic communities between wetlands created by an agricultural water recycling system - Peter C. Smiley; Barry J. Allred (Wetlands Ecology and Management, 2011)

Yield development and nutrient dynamics in cocoa-gliricidia agroforests of Central Sulawesi, Indonesia - G. L. Smiley; J. Kroschel (Agroforestry Systems, 2010)

Temporal change in carbon stocks of cocoa–gliricidia agroforests in Central Sulawesi, Indonesia - G. L. Smiley; J. Kroschel (Agroforestry Systems, 2008)

Techniques for live capture of deepwater fishes with special emphasis on the design and application of a low‐cost hyperbaric chamber - J. E. Smiley; M. A. Drawbridge (Journal of Fish Biology, 2007)
A cost effective, simple, portable hyperbaric chamber was constructed from polyvinyl chloride to aid in the collection of adult rockfishes Sebastes sp. to hold as broodstock. This system was designed to recompress fishes quickly once brought to the surface on hook and line, and to allow for decompression over a period of days. The hyperbaric chamber is capable of continuous stable operation at −2 and can accommodate fishes up to 91·4 cm in length and 26·8 cm in diameter. Pressure in the chamber is maintained by a Goulds Booster pump that delivers continuous pressure and supplies sea water at a rate of 3·8 to 7·6 l min −1 to as many as four chambers. The hyperbaric chamber operated very effectively and allowed successful decompression of 12 cowcod Sebastes levis captured at depths of 90·2 to 146·3 m.

Changing plans: neural correlates of executive control in monkey and human frontal cortex - Elisa C. Dias; Tammy McGinnis; John F. Smiley; John J. Foxe; Charles E. Schroeder; Daniel C. Javitt (Experimental Brain Research, 2006)

Control of aperture closure during reach-to-grasp movements in parkinson’s disease - M. K. Rand; A. L. Smiley-Oyen; Y. P. Shimansky; J. R. Bloedel; G. E. Stelmach (Experimental Brain Research, 2006)

Attraction of two lacewing species to volatiles produced by host plants and aphid prey - J. Zhu; J. J. Obrycki; Samuel A. Ochieng; Thomas C. Baker; J. A. Pickett; D. Smiley (The Science of Nature, 2005)

Motor learning processes in a movement-scaling task in olivopontocerebellar atrophy and Parkinson's disease - A. L. Smiley-Oyen; C. J. Worringham; C. L. Cross (Experimental Brain Research, 2003)

Comparative Responses of Parasitoids to Synthetic and Plant-Extracted Nepetalactone Component of Aphid Sex Pheromones - R. T. Glinwood; Y.-J. Du; D. W. M. Smiley; W. Powell (Journal of Chemical Ecology, 1999)

Sex Pheromone Stereochemistry and Purity Affect Field Catches of Male Aphids - Jim Hardie; Lynn Peace; John A. Pickett; Diane W. M. Smiley; J. Robert Storer; Lester J. Wadhams (Journal of Chemical Ecology, 1997)

ThePassiflora problem in Hawaii; prospects and problems of controlling the forest weedP. Mollissima [Passifloraceae] with heliconiine butterflies - J. K. Waage; J. T. Smiley; L. E. Gilbert (BioControl, 1981)

Heterothallism in Pichia kudriavzevii and Pichia terricola - C. P. Kurtzman; M. J. Smiley (Antonie van Leeuwenhoek, 1976)